2012
DOI: 10.1063/1.4730906
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen adsorbed in a metal organic framework-5: Coupled translation-rotation eigenstates from quantum five-dimensional calculations

Abstract: We report rigorous quantum five-dimensional (5D) calculations of the coupled translation-rotation (T-R) eigenstates of a H(2) molecule adsorbed in metal organic framework-5 (MOF-5), a prototypical nanoporous material, which was treated as rigid. The anisotropic interactions between H(2) and MOF-5 were represented by the analytical 5D intermolecular potential energy surface (PES) used previously in the simulations of the thermodynamics of hydrogen sorption in this system [Belof et al., J. Phys. Chem. C 113, 931… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(77 citation statements)
references
References 84 publications
3
74
0
Order By: Relevance
“…This type of calculation was previously used to predict the rotational transitions for H 2 sorbed in various MOFs. 52,53,69,[71][72][73][74][75][76][77][78] Here, the results are discussed for calculations using the polarizable H 2 potential. For H 2 sorbed at site 1 in ZIF-68, a rotational energy level of 6.95 meV was calculated for the transition between j = 0 and the lowest j = 1 sublevel (Table S8).…”
Section: Rotational Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of calculation was previously used to predict the rotational transitions for H 2 sorbed in various MOFs. 52,53,69,[71][72][73][74][75][76][77][78] Here, the results are discussed for calculations using the polarizable H 2 potential. For H 2 sorbed at site 1 in ZIF-68, a rotational energy level of 6.95 meV was calculated for the transition between j = 0 and the lowest j = 1 sublevel (Table S8).…”
Section: Rotational Dynamicsmentioning
confidence: 99%
“…The higher than expected calculated value of the j = 0 to j = 1 transition for H 2 sorbed at site 1 in ZIF-69 could result from the theoretical potential energy surface for the adsorbent or the lack of coupling to translational motion, which has shown to be important in certain cases. 71 We emphasize again that the region between the two adjacent 2-nitroimidazolate linkers in ZIF-69 imposes a high barrier to rotation on the H 2 molecule as in ZIF-68. A rotational barrier of 39.38 meV was calculated for H 2 sorbed at site 1 in ZIF-69 ( Figure S17), which is also greater than those for many MOFs according to previous INS studies.…”
mentioning
confidence: 99%
“…Besides H 2 @C 60 , the theoretical study of which will be reported shortly, this includes molecular hydrogen in clathrate hydrates [19,29,30], metal-organic frameworks [31][32][33][34][35] and zeolites [36,37], among others. Finally, methodological extensions are in progress in our group to the INS spectra of nanoconfined polyatomic molecules such as methane [38] and water [39].…”
Section: Discussionmentioning
confidence: 99%
“…3,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] More recently, studies have appeared focusing on different adsorbates, such as CO, CH 4 , CO 2 , SO 2 , or H 2 O, and different substrates such as zeolites and metal-organic frameworks. 7,[23][24][25][26][27][28] One particular feature present in single-walled carbon nanotubes (SWCNTs) that makes them especially interesting materials is their cylindrical shape, which gives rise to the coexistence of a 2D confinement in the space perpendicular to the nanotube's axis and unbound motion along this latter coordinate. Even though 2D confinement has been relatively studied and reviewed in the literature, 12,16,29,30 only few studies have treated both the confined and the quasi-free coordinates in a fully quantum formalism.…”
Section: Introductionmentioning
confidence: 99%